Dietary diversity and its determinants among Khasi and Garo indigenous women (15 to 49 years) in Meghalaya, northeast India - Nongrum, Melari Shisha; Pawera, Lukas; Mawroh, Bhogtoram (Nutrition and health, 2022)
BACKGROUND: Despite generally high agrobiodiversity, the Khasi and Garo indigenous people in Meghalaya have poor nutritional status among children and women. AIM: To assess the dietary diversity of the Khasi and Garo indigenous women of reproductive age in Meghalaya, while examining the associated factors that affect it and to map the diversity of local food plants. METHODS: A dietary survey was conducted through 24-hour recall with 276 women from 28 villages of Meghalaya. The mapping of local food plants was conducted through key informant interviews and focus group discussions in the same villages. RESULTS: The mean minimum dietary diversity for women is 4.22 (SD ±1.26); with one-third (37%) of the women attaining a minimum dietary diversity of five or more food groups in a day. There were significant differences in the dietary diversity among the indigenous groups, the Garo community attaining higher minimum dietary diversity for women. There was also an inverse association between the number of land uses and dietary diversity. The mean number of food plants (including crop varieties) found in each village is 203 (SD±45.7). CONCLUSIONS: There is potential to enhance dietary diversity through diversifying lesser consumed crops such as vitamin A-rich vegetables and fruits, nuts, seeds and green leafy vegetables in existing land holdings. Also, proper management and access to the commons will provide a sustainable resource base for diet and food security, enhance dietary diversity and bridge the hidden hunger among children and women.
Keywords: Diet; dietary diversity in Meghalaya; Garo women; indigenous food; ovoce; lidé; Humans; Child; zelenina; Khasi women; Fruit; dieta; Vegetables; Malnutrition; indigenous women; dítě; agrobiodiversity; ženské pohlaví; Indie; podvýživa; Female; India; Dietary diversity